Dissonance as a Concept of Preserving the Architectural heritage: Case Study of the Belgrade Fairground - Slavić, Stefan (Arhitektura i urbanizam, 2021)
Belgrade Fairground, built in the 1930s, was the first urban complex designed according to modern principles and the first physical structure built in Belgrade on the left bank of the Sava. During its existence, the complex has undergone radical changes - from a fairground, through a concentration camp during World War II, an art colony in the post-war period, to its current state as a marginalized urban segment inhabited by the homeless, with uncontrolled commercial development . These transformations over time have resulted in the creation of numerous layers of identity, which, from a contemporary point of view, the space itself should testify to. The paper examines the transformations that have taken place in the space, and refers to the mutually opposed events that to some extent have hindered the recovery and development of the former Belgrade Fairground. The paper, in the form of a case study, analyzes the space by exploring the application of dissonance in preserving and revitalizing the architectural heritage, since the concept of dissonance is important for articulating opposing meanings and emphasizing the plurality of values. In order to shed light upon all the characteristic phases of the complex’s existence, its morphological transformations and then its functional transformations were analyzed, followed by a presentation of how its social relationship with the Belgrade Fairground has been transformed. Accordingly, the ultimate goal was to find a way to manifest the diversity of the fairground’s value and its re-perception as belonging to the urban space.
Keywords: Belgrade Fairground, Transformations, Dissonance, Architectural Heritage